2009
DOI: 10.1111/j.1365-2958.2009.06625.x
|View full text |Cite
|
Sign up to set email alerts
|

Menaquinone synthesis is critical for maintaining mycobacterial viability during exponential growth and recovery from non‐replicating persistence

Abstract: Summary Understanding the basis of bacterial persistence in latent infections is critical for eradication of tuberculosis. Analysis of Mycobacterium tuberculosis mRNA expression in an in vitro model of non-replicating persistence indicated that the bacilli require electron transport chain components and ATP synthesis for survival. Additionally, low μM concentrations of aminoalkoxydiphenylmethane derivatives inhibited both the aerobic growth and survival of non-replicating, persistent M. tuberculosis. Metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(167 citation statements)
references
References 51 publications
(83 reference statements)
4
149
1
Order By: Relevance
“…4A). MenH catalyzes the methylation of demethylmenaquinol to menaquinol, the major electron carrier in Mtb's electron transport chain (25). We detected a significant down-regulation of genes involved in respiration (Fig.…”
Section: Significancementioning
confidence: 59%
See 2 more Smart Citations
“…4A). MenH catalyzes the methylation of demethylmenaquinol to menaquinol, the major electron carrier in Mtb's electron transport chain (25). We detected a significant down-regulation of genes involved in respiration (Fig.…”
Section: Significancementioning
confidence: 59%
“…Also biosynthesis of mycolic acid, an essential component of the mycobacterial cell wall, or menaquinone, the electron carrier in the electron transport chain, have an absolute requirement for SAM (25,43). Many of these processes are validated drug targets in Mtb (25,26,(44)(45)(46). The possibility that the upstream accumulation of a toxic metabolite might contribute to the killing cannot be ruled out, but so far such a compound could not be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common menaquinones contain 7, 8 or 9 isoprene units, however, menaquinones with 4, 5, 6, 10, 11, 12 or 13 isoprene units have been isolated from bacteria. Since it has been demonstrated that menaquinone is crucial for bacterial growth (Dhiman et al 2009;Fujimoto et al 2012) and colony development (Pelchovich et al 2013), it is not a surprise that menaquinone biosynthesis has already been investigated as a target for the development of novel antibiotics (Kurosu and Begari 2010). In the last years a few inhibitors of individual enzymes of menaquinone biosynthesis have been reported (Kurosu and Begari 2010).…”
Section: Menaquinone As a Small Molecule Antibacterial Targetmentioning
confidence: 99%
“…It has been recognized that understanding important metabolic pathways is likely to be a useful route towards new therapies (www.tballiance.org) as a result of the success with an ATPase inhibitor (Diacon et al, 2009). Recent identification of menaquinone biosynthesis as a useful target pathway provides a growing portfolio of potential novel anti-tuberculars (Dhiman et al, 2009). The need for a wide range of candidate targets and molecular classes is insurance for the future (Maxmen and Barry, 2009;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%